Characterisation of a new tumorous-head mutant of Drosophila melanogaster. - Bownes, M.; Roberts, S.; Dempster, M.; Bournias-Vardiabasis, N. (Molecular and General Genetics, 1981)
A new homoeotic mutant, I127, showing abnormal growths in the head region including homoeotic transformation of eye to genitalia and antenna to leg, was isolated in a screen designed to find new alleles of the tumourous head (tuh-3), mutation. Similarities in the phenotype and genetics of the mutant, and complementation studies with tuh-I; tuh-3, suggest that I127 is indeed an allele of tuh-3. In combination with the first chromosome modifier tuh-1, the mutant is temperature-sensitive during the third larval instar, giving an increased penetrance of the tumorous head phenotype when reared at 25 degrees C as opposed to 18 degrees C. The isolation of further alleles at the tumorous-head locus are essential. The type of morphological defects which can result from mutations at this locus would enable us to establish if this is a complex locus, and if null mutations are lethal during development. The interactions of the tumorous-head gene with first chromosome modifiers and other homoeotic mutations will only be understood if we are able to induce a number of mutations at this locus, and as a consequence begin to elucidate the role of the wild-type gene product in normal development.